Learning from AI Failures: A Critical Analysis of Enterprise AI Implementation - Vinay Kumar Ankusarao, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article presents a comprehensive analysis of an enterprise-scale artificial intelligence implementation failure at a leading service industry organization. The article examines a proof-of-concept project aimed at transforming customer success operations through AI-powered insights and recommendations. Through detailed examination of the technical architecture, implementation methodology, and failure points, this article identifies critical challenges in data quality, system integration, and scalability that led to the project's unsuccessful outcome. The analysis provides valuable insights into enterprise AI implementation prerequisites and offers technical recommendations for future implementations. Drawing from cross-industry experiences, particularly in healthcare and HR domains, the study establishes a framework for successful AI adoption while highlighting the importance of robust data infrastructure, phased development approaches, and comprehensive validation frameworks. The article findings contribute to the growing body of knowledge on enterprise AI implementation strategies and provide practical guidelines for organizations embarking on similar digital transformation initiatives.
Keywords: Enterprise AI Implementation; Data Quality Management; System Architecture; Digital Transformation; Implementation Framework